Economic mobility, family background, and the well-being of children in the United States and Canada - Miles Corak; Lori Curtis; Shelley Phipps (Institute for the Study of Labor (IZA), 2010)
This comparative study of the relationship between family economic background and adult outcomes in the United States and Canada addresses three questions. First, is there something to explain? We suggest that the existing literature finds that there are significant differences in the degree of intergenerational economic mobility between these two countries, relative mobility being lower in the United States. This is the result of lower mobility at the very top and the very bottom of the earnings distribution. Second, does this reflect different underlying values of the citizens in these countries? Findings from comparable public opinion polls suggest that this is not the case. The citizens of both countries have a similar understanding of a successful life, one that is rooted in individual aspirations and freedom. They also have similar views on how these goals should be attained, but with one important exception: Americans differ in that they are more likely to see the State hindering rather than helping the attainment of these goals. Finally, how do the investments these countries make in the future of their children through the family, the labour market, and public policy actually differ? Using a number of representative household surveys we find that the configuration of all three sources of investment and support for children differs significantly, disadvantaged American children living in much more challenging circumstances, and the role of public policy not as strong in determining outcomes.
Keywords: J62; J13; I3; 330; Intergenerational mobility; children; Canada; United States; Soziale Mobilität; Intergenerational Mobility; Familiensoziologie; Kinder; Lebensstandard; USA; Kanada